A Fluorimetric Readout Reporting the Kinetics of Nucleotide‐Induced Human Ribonucleotide Reductase Oligomerization. Issue 17 (24th September 2014) - Fu, Yuan; Lin, Hong‐Yu; Wisitpitthaya, Somsinee; Blessing, William A.; Aye, Yimon
Abstract Human ribonucleotide reductase (hRNR) is a target of nucleotide chemotherapeutics in clinical use. The nucleotide‐induced oligomeric regulation of hRNR subunit α is increasingly being recognized as an innate and drug‐relevant mechanism for enzyme activity modulation. In the presence of negative feedback inhibitor dATP and leukemia drug clofarabine nucleotides, hRNR‐α assembles into catalytically inert hexameric complexes, whereas nucleotide effectors that govern substrate specificity typically trigger α‐dimerization. Currently, both knowledge of and tools to interrogate the oligomeric assembly pathway of RNR in any species in real time are lacking. We therefore developed a fluorimetric assay that reliably reports on oligomeric state changes of α with high sensitivity. The oligomerization‐directed fluorescence quenching of hRNR‐α, covalently labeled with two fluorophores, allows for direct readout of hRNR dimeric and hexameric states. We applied the newly developed platform to reveal the timescales of α self‐assembly, driven by the feedback regulator dATP. This information is currently unavailable, despite the pharmaceutical relevance of hRNR oligomeric regulation.